Enacting Social Justice Leadership Through Teacher Hiring - Laura, Crystal T. (The Urban review, 2018)
Drawn from a compendium of multiple cases, this single-subject qualitative study offers a nuanced depiction of the ways school principals advocate for social justice through teacher hiring. The hiring experiences of one Hispanic female high school principal was used to explore: (a) the principal’s approach to school personnel administration to promote social justice, including the processes, policies, and practices regarding teacher recruitment and selection and (b) the meanings the principal attaches to this approach and its perceived impact.